(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This article looks at what outsourcing is, how it works, and why it matters for hotels and tourism companies. We also look at how outsourcing is developing in Uzbekistan right now. The paper is based on existing research and official data. We find that outsourcing has real benefits for the hospitality sector but there are also problems that need to be solved before it can grow properly in our country.